2009
DOI: 10.1159/000243050
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Matrix-Metalloproteinases in Patients with Chronic Kidney Disease: Are They Associated with Cardiovascular Disease?

Abstract: Background: High cardiovascular risk in patients with chronic kidney disease (CKD) may be related to mineral disorder and microinflammation. Fibroblast growth factor 23 (FGF-23) is a phosphatonin and inhibitor of calcitriol synthesis, which is associated with poor prognosis in CKD patients starting dialysis. Matrix-metalloproteinases (MMP-2, MMP-9) contribute to myocardial remodeling and arterial calcification. FGF-23 and MMPs levels are altered in CKD, however, little is known about their association and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Serum MMP-2 concentrations in the examined population were elevated, when compared to controls, similar to the results obtained in adults by others (Peiskerova et al 2009; Chang et al 2006). The novelty of our observation was the fact that MMP-2 levels increased gradually with the progression of CKD and correlated with GFR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serum MMP-2 concentrations in the examined population were elevated, when compared to controls, similar to the results obtained in adults by others (Peiskerova et al 2009; Chang et al 2006). The novelty of our observation was the fact that MMP-2 levels increased gradually with the progression of CKD and correlated with GFR.…”
Section: Discussionsupporting
confidence: 91%
“…Chang et al (2006) found decreased levels of gelatinase B, whereas Peiskerova et al (2009) noticed no difference between controls and CKD patients. In our group, a gradual increase was observed, together with an inverse correlation to GFR values.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al [18] also found a positive correlation between patient serum phosphorus levels and MMP-2 expression in the inferior epigastric arteries. Similarly, in CKD patients there was a positive relationship of hyperphosphatemia with serum MMP-2 levels [20]. However, we found increased tissue expression early in the course of CKD when the animals were not yet hyperphosphatemic.…”
Section: Discussionmentioning
confidence: 51%
“…FGF23 levels are elevated early in CKD and increase as the disease progresses [2]. Increased circulating FGF23 levels are associated with an increased risk of peripheral vascular calcification [3], heart disease [4-9] and death [10-12]. In animal models, FGF23 can directly induce left ventricular hypertrophy, which can be prevented by blocking the intracellular signaling pathway stimulated by FGF23 [13].…”
Section: Introductionmentioning
confidence: 99%